2014
DOI: 10.1038/srep06250
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the near-surface superfluid density in underdoped YBa2Cu3O6+x by photo-illumination

Abstract: The interaction with light weakens the superconducting ground state in classical superconductors. The situation in cuprate superconductors is more complicated: illumination increases the charge carrier density, a photo-induced effect that persists below room temperature. Furthermore, systematic investigations in underdoped YBa2Cu3O6+x (YBCO) have shown an enhanced critical temperature Tc. Until now, studies of photo-persistent conductivity (PPC) have been limited to investigations of structural and transport p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…2. To illuminate the samples, either LEDs or solid-state lasers are available [7,25,26]. For illumination with blue light, we use either a LED source with λ = 405 nm (Bluepoint, Hönle AG, Gräfeling, Germany) or a diode pumped solid-state laser with λ = 457 nm.…”
Section: Methodsmentioning
confidence: 99%
“…2. To illuminate the samples, either LEDs or solid-state lasers are available [7,25,26]. For illumination with blue light, we use either a LED source with λ = 405 nm (Bluepoint, Hönle AG, Gräfeling, Germany) or a diode pumped solid-state laser with λ = 457 nm.…”
Section: Methodsmentioning
confidence: 99%
“…2. To illuminate the samples, either LEDs or solid state lasers are available [7,24,25]. For illumination with blue light we used either a LED source with λ = 405 nm (Bluepoint, Hönle AG, Gräfeling, Germany) or a diode pumped solid state laser with λ = 457 nm.…”
Section: Methodsmentioning
confidence: 99%
“…11 is a way of a model-independent B-vs-z mapping. It has been demonstrated that subtle effects can, indeed, be measured by measuring the effects of photopersistent conductivity on Meissner screening in YBa 2 Cu 3 O 6+x (Stilp et al, 2014a), as well as the effects of gold nano-particle doping in YBa 2 Cu 3 O 7−δ , leading to increased Meissner screening (Stilp et al, 2014b). Kiefl et al (2010) measured the anisotropy of the London penetration depth in YBa 2 Cu 3 O 7−δ single crystals, which allows separating the contribution of the superconducting chains present in this compound.…”
Section: Frontiers In Electronic Materialsmentioning
confidence: 99%